Highly Selective and Sensitive Fluorescent Turn-on Chemosensor for Al3+ Based on a Novel Photoinduced Electron Transfer Approach - Lu, Yan; Huang, Shanshan; Liu, Yiyang; He, Song; Zhao, Liancheng; Zeng, Xianshun (Organic letters, 2011)
A photoinduced electron transfer (PET)-based chemosensor possessing dual PET processes by simultaneously introducing both nitrogen and sulfur donors was achieved. The fluorescence signal of the free chemosensor is in a normal-off state due to the sulfur donor being insensitive to environmental pH stimuli. As a result, the device can be used over a wide pH span of 3–11. Upon binding Al3+, a significant fluorescence enhancement with a turn-on ratio over 110-fold was triggered by the inhibition of PET processes from both the sulfur and the nitrogen donors to the fluorophore.